Estrategias utilizadas por profesoras que enseñan en preescolar para el desarrollo del pensamiento numérico: una mirada desde la Educación Inicial - González Valencia, Heriberto (Universidad Santiago de Cali, 2017)
This study was to describe the strategies used by teachers teaching in Pre-school for the development of mathematical thinking in Initial Education. The context of this study was done in two different places: The teacher's house 1 and the Caritas Felices children's home located in the city of Cali, Colombia, where teacher 2 did her practice. This study is framed under the qualitative method; the procedures for data collection were observation and interview. The results show that the teachers who teach in Preschool implemented di-fferent teaching strategies, which were identified and described. In addition, the teachers who participated in this study stated that each of the strategies implemented in the development of the different tasks had certain intentions when they were used.